Crystallographic, structural, optical, and dielectric properties of aniline and aniline halide imprinted hydrogels for optoelectronic applications - Yalcin, Orhan; Coskun, Ramazan; Okutan, Mustafa; Oncan, Mehmet; Yesilot, Gursel (SPRINGER, 2023)
This study examines the availability of aniline and aniline halide imprinted hydrogels for technological applications through crystallographic, structural, optical, and dielectric studies. Their optical band gap and ultraviolet-visible (UV-Vis) absorption spectra have been performed in the wavelength range of 190-900 nm. The dielectric properties, energy loss tangent/ dissipation factor (tand), and complex electric modulus were characterized at room temperature and a frequency range of 100 Hz to 100 MHz. The results suggest that the complex dielectric constant and modulus are related to Kroop's theory, Brownian motion in viscoelastic systems, and Maxwell-Wagner theory. Conductivity parameters and negative s-parameter values were obtained, providing insight into the conductivity mechanism of the samples. The Cole-Davidson plots of the complex dielectric constant and the Cole-Davidson plots adapted to Smith Chart diagrams were obtained to observe the sufficiency of the samples in electronic circuit applications. Overall, the study provides a detailed analysis of the dielectric, morphological, and optical properties of aniline and aniline halide imprinted hydrogels, demonstrating their potential for technological applications.
Keywords: SHIELDING CAPABILITY; SYNTHETIC CIRCUITS; DOPED HYDROGELS; IMPEDANCE; CONDUCTIVITY; FREQUENCY; NANOPARTICLES; SPECTROSCOPY; ELECTROLYTE; CAPACITANCE; Engineering; Materials Science; Physics